Effect of Kangaroo Care in Preterm Infants on Breast Milk Volume - Daramas, Tipawan; Wittayasooporn, Jariya; Khamsripon, Chalinda (Journal of The Royal Thai Army Nurses, 2020)
The purpose of this quasi-experimental design research was to compare breast milk volume of the mothers of preterm infants received kangaroo care with those who received usual nursing care. The samples consisted of 32 mothers and premature infants. The samples were purposively selected and divided into control group and experimental group. Research tools were 1) general information questionnaire, 2) pain assessment, 3) self-stress assessment and 4) breast milk recording form. Data were analyzed by descriptive statistics and independent t-test. The result of the study revealed that the average of breast milk volume of the mothers receiving kangaroo care was 4,544.20 (S.D. = 1519.77) while that of those receiving normal nursing care was 2,616. 25 ml (S.D. = 844.36). When milk volume was compared, the average amount of breast milk of the mothers receiving kangaroo care was higher than that of the mothers receiving usual nursing care with statistical significance (p < .001).